Planning a Sustainable City: The Making of Curitiba, Brazil. (November 2013) - Macedo, Joseli
Curitiba, Brazil, is recognized as a model of urban planning. The city's innovative practices have been internationally praised for the past twenty years, although the first plans that enabled the urban form that Curitiba has today are rarely acknowledged. Sustainable initiatives were implemented in Curitiba before sustainability became the preferred alternative for development; however, the people behind Curitiba's innovations have not been properly recognized. This article provides a historical overview of all the urban plans that have made the Curitiba paradigm possible. It also recounts Curitiba's urban development and planning history through the voices of some of the people who contributed to making it the city that it is today. In addition to archival research, a series of interviews reveals their stories and memories of the experience of planning a city to be the best it can be. Their commentary on Curitiba's future suggests the work is not done. The article concludes with an appraisal of sustainability within the Curitiba context.